Comparative Analysis of Chemical Constituents in Different Parts of Lotus by UPLC and QToF-MS - Haotian Pei; Wenyu Su; Meng Gui; Mingjie Dou; Yingxin Zhang; Cuizhu Wang; Dan Lu (Molecules, 2021)
Six parts of lotus (seeds, leaves, plumule, stamens, receptacles and rhizome nodes) are herbal medicines that are listed in the Chinese Pharmacopoeia. Their indications and functions have been confirmed by a long history of clinical practice. To fully understand the material basis of clinical applications, UPLC-QToF-MS combined with the UNIFI platform and multivariate statistical analysis was used in this study. As a result, a total of 171 compounds were detected and characterized from the six parts, and 23 robust biomarkers were discovered. The method can be used as a standard protocol for the direct identification and prediction of the six parts of lotus. Meanwhile, these discoveries are valuable for improving the quality control method of herbal medicines. Most importantly, this was the first time that alkaloids were detected in the stamen, and terpenoids were detected in the cored seed. The stamen is a noteworthy part because it contains the greatest diversity of flavonoids and terpenoids, but research on the stamen is rather limited.